Digital Parenting: Pelatihan Kompetensi Pengasuhan Orang Tua (Parenting) Anak Usia Dini di Era Milenial - Gian Fitria Anggraini; Een Y Haenilah; Ari Sofia; Rizky Drupadi (Universitas Mathla'ul Anwar Banten, 2021)
DIGITAL PARENTING: EARLY CHILDHOOD PARENTING COMPETENCY TRAINING IN THE MILLENNIAL ERA. This parenting program aimed to provide understanding and accompaniment of educators parenting competencies, especially in the digital era. Specifically, the objectives of this training are: (1) parents and teachers can apply an effective parenting method for early childhood (2) parents and teachers can implement consistent and complementary parenting strategies at home and at school in accordance with the needs of early childhood in the digital era; and (3) parents and teachers are able to use technology as a friendly method of childcare. The method chosen in this training activity was providing training and mentoring for parenting competencies either through counseling, discussions, evaluation stimulations and assignments. The training was carried out in several stages, namely, the initial stage (socialization), the implementation stage, and evaluation. The training participants were 20 parents and teachers of Dharma Wanita Kindergarten, Lab School University of Lampung. The results showed that 85% of participants experienced an increase in their scores before and after the training. The average of pre and post-test increased by 2.4 points. The results of different tests (t-test) also showed that there are significant differences (sig 0.00) and improvements related to the understanding of parents and teachers regarding the use of gadgets or technology and parenting of early childhood in millennial era, before and after receiving training.